The impact of altitude on hospitalization and hospital mortality from pandemic 2009 influenza A (H1N1) virus pneumonia in Mexico El impacto de la altitud en las tasas de hospitalización y mortalidad por el virus de la influenza A (H1N1) pandémico en México - Rogelio Pérez-Padilla; Cecilia García-Sancho; Rosario Fernández; Francisco Franco-Marina; Hugo López-Gatell; Ietza Bojórquez (Instituto Nacional de Salud Pública, 2013)
OBJECTIVE: To determine the effect of altitude of residence on influenza A (H1N1). MATERIALS AND METHODS: We analyzed 207 135 officially notified of influenza-like illness (ILI) cases, 23 048 hospitalizations and 573 deaths during the first months of the novel pandemic influenza A H1N1 virus, to examine if residents of high altitude had more frequently these adverse outcomes. RESULTS: Adjusted rates for hospitalization and hospital mortality rates increased with altitude, probably due to hypoxemia. OBJETIVO: Determinar el efecto de la altitud del lugar de residencia sobre la epidemia de influenza A (H1N1). MATERIAL Y MÉTODOS: Se analizaron 207 135 casos notificados a la Secretaría de Salud, 23 048 hospitalizaciones y 573 muertes por enfermedad similar a la influenza (ILI, por sus siglas en inglés) durante los primeros meses de la pandemia del nuevo virus de la influenza A H1N1 durante 2009, para examinar si los residentes de zonas más altas presentaron tasas más altas de hospitalización y muerte. RESULTADOS: Las tasas ajustadas de hospitalización y mortalidad hospitalaria se incrementaron con la altitud probablemente por la presencia de hipoxemia.